Kajian terhadap Model Permainan Bulutangkis untuk Siswa SMP Negeri 2 Kota Gorontalo - Arman Arman; Hariadi Said; Rosbin Pakaya (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
The challenges of teaching badminton in schools include limited facilities, a lack of appropriate teaching methods or models, low student interest, and limited creativity among teachers in managing instruction to make it more interesting and meaningful. This study aims to examine badminton teaching methods that are suitable for the characteristics of students at SMP Negeri 2 Gorontalo. A qualitative descriptive approach was applied to achieve the objectives of this study. The stages of this study were data collection, data reduction, data presentation, and conclusion drawing. The results of the study show that the bukisteja game model, which is a combination of badminton and table tennis, can be an innovative alternative that supports active, participatory, and student-centered learning. This game is designed in a 3-on-3 format using a standard badminton court and applies a player rotation and rally point system to increase the involvement of all students. Pedagogically, this model contributes to the development of cognitive aspects (understanding rules and strategies), affective aspects (sportsmanship, discipline, and cooperation), and psychomotor aspects (coordination, agility, stroke technique, and reflexes). In addition, the application of structured game rules helps shape students' character through compliance, responsibility, and sportsmanlike game management. Keywords: Badminton, Game, Junior High School Students, Model